2021
DOI: 10.1002/smll.202105387
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Microenvironment of Asymmetric N,S‐Coordinated Single‐Atom Fe via Axial Fifth Coordination toward Efficient Oxygen Electroreduction

Abstract: Single‐atom catalysts (SACs) are attractive candidates for oxygen reduction reaction (ORR). The catalytic performances of SACs are mainly determined by the surrounding microenvironment of single metal sites. Microenvironment engineering of SACs and understanding of the structure–activity relationship is critical, which remains challenging. Herein, a self‐sacrificing strategy is developed to synthesize asymmetric N,S‐coordinated single‐atom Fe with axial fifth hydroxy (OH) coordination (Fe−N3S1OH) embedded in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 92 publications
2
65
0
Order By: Relevance
“…To date, two general pathways are developed to optimize the electronic structure of FeN 4 active sites. One is directly replacing partial coordinated N atoms in FeN 4 with other heteroatoms (e.g., S [ 24 ] and P [ 25 ] ) to construct an asymmetrically coordinated Fe active site. The other strategy is utilizing the long‐range interactions to modify the electronic structure of the FeN 4 active center.…”
Section: Introductionmentioning
confidence: 99%
“…To date, two general pathways are developed to optimize the electronic structure of FeN 4 active sites. One is directly replacing partial coordinated N atoms in FeN 4 with other heteroatoms (e.g., S [ 24 ] and P [ 25 ] ) to construct an asymmetrically coordinated Fe active site. The other strategy is utilizing the long‐range interactions to modify the electronic structure of the FeN 4 active center.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the energy changes of the PDSs, namely desorption of ∗OH, decrease to 0.50 and 0.36 eV on Fe- and Co-complexes, related to improved oxygen reduction performance. In experiment, it has been also reported that the ultimate ORR performance is achieved by constructing a single atom catalyst with coordination number of five ( Han et al., 2018 ; Li et al., 2022 ). In contrast, Ni 2+ cation possesses d 8 electron configuration.…”
Section: Resultsmentioning
confidence: 99%
“…The coordination environment of single atom and atomic cluster on LD materials can significantly alter the electronic properties of the active sites. Tuning the coordination environment of single atoms to achieve high activity and selectivity is becoming a hot topic in both theoretical [187,188] and experimental [189,190] parts. Ha et al employed the high-throughput computation and machine learning methods to explore the stability and activity of TM supported on nitrogen-doped graphene (TM-GN) for HER, OER, and ORR.…”
Section: Support and Coordination Effectmentioning
confidence: 99%